Kimura’s disease: a case report - Zablon Mesfin Anbessie (Journal of Medical Case Reports, 2024)
Abstract Background Kimura’s disease is a rare chronic inflammatory disorder of unknown etiology that is seen in people of Asian descent. It is characterized by head and neck subcutaneous nodules along with lymphadenopathy, which is usually solitary but can be generalized. It is diagnosed histopathologically by the proliferation of blood vessels and germinal centers in lymphoid follicles, along with variable degrees of fibrosis and extensive eosinophil infiltration. Its localized form is treated with surgical excision, while generalized lesions and those that do not respond to surgical excision can be managed with steroids or radiotherapy. Case In this report, we present the first case of Kimura’s disease in the Ethiopian literature in a 40-year-old Ethiopian man that presented with generalized pruritic subcutaneous nodules and lymphadenopathy, which were effectively managed with a tapering course of prednisolone, and a relapse that showed good sustained response with slow steroid taper. Conclusion We have demonstrated that, even though it is very rare in the African continent, Kimura’s disease is to be considered as a differential diagnosis for patients that present with subcutaneous nodules and lymphadenopathy. We also have demonstrated that relapses can be effectively managed with reinitiation of the same dose of steroids but with a very slow taper.